Buyhid conflicts in the era of the sons of Adud-Dawlah and its repercussions (372-403 AH / 982-1012 AD) - مرعي , سامي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This paper deals with the Buyid-Buyid conflicts in the era of the Adud al-Dawlah sons who took power in Baghdad, and they are: Samsam al-Dawlah (372- 376 AH / 982- 986 AD), Sharaf al-Dawlah (376- 379 AH / 986- 989 AD), and Baha al-Dawlah (379- 403 AH / 989-1012 AD), investigating the reasons for these Conflicts, then dealt with its events in detail, presenting the conflict between the two brothers Samsam al-Dawlah and the Sharaf al-Dawlah, then the Buway-Buway conflicts in the era of the Sharaf al-Dawlah, and then during the reign of Baha al-Dawlah, especially the conflict between him and his nephew, Abu Ali bin Sharaf al-Dawlah, between him and his uncle Fakhr al-Dawlah, Between him and his brother Samsam al-Dawlah, then between Samsam al-Dawlah and the children of Izz al-Dawlah Bakhtiar, and finally the conflict between Baha al-Dawlah and the children of Izz al-Dawlah Bakhtiar. The research examines the effects and repercussions of these conflicts on Buihi rule, as they led to the disintegration of the Buyhid family, the weakness of its rule and its turmoil, the absence of the authority of the Buihi prince and the demise of his prestige, the increase in the influence of the army, the occurrence of multiple internal strife represented in the movements of caliber and religious strife, the occurrence of economic crises, the high cost of living and the rise In terms of prices, and the emergence of independent emirates from the Buihi rule in the periphery, And the Fatimid influence increased in strength in the Bilad Al-Sham, its expansion towards the AL- Jazira, and its access to the areas of the Abbasid Caliphate and the Buyhid rule.